Stress In University Libraries: A Study of University of Professional Studies, Accra and Wisconsin International University College-Ghana. - Okai, R. (University of Ghana, 2015)
The study looks at stress in university libraries. Universities have experienced exponential growth in student population as more programmes had been introduced lately. The increase had not been matched with infrastructure, staff and funding. This situation had made the job of the library very stressful. Stress, is referred to as a state of psychological and or physical imbalance resulting from the disparity resulting from the disparity between situational demand and the individual’s ability to meet those demands. Modern world individuals are experiencing long- term unacceptable high levels of arousal which give rise to chronic stress which every class of people are no exception. The study aimed to identify the main stressors that cause stress for the professional librarians and paraprofessionals of UPSA and WIUC-Gh and investigate the coping strategies that they employed to control their stressors with the view of making recommendations to enhance stress coping capabilities. The study adopted the Bio-Psychosocial Model of Stress Theory which provides a realistic explanation of the complicated nature of stress. To achieve the objectives of the research, the study used a qualitative method approach complemented by observation. All the library professionals and paraprofessionals of the two universities were interviewed. The study found out that the library work itself, unfavourable working environment, work overload and challenges in relation to users, rudeness of patrons. Other sources of stress found were traffic congestion and job dissatisfaction. In addition, the study established that the library staff stress levels were not high because they had all attended library school and had combined their professionalism with effective coping strategies. The study concluded that if the managements of both universities would be able to provide adequate equipment and resources, favourable working environment, comprehensive orientation to new students, employment of more staff the library staff will be able to work without much stress. The study recommended provision of requisite resources, favourable working environment, employment of more staff, recruitment of part-time workers during examination period and seminars on stress management.
Thesis (MPhil) - University of Ghana, 2015
Keywords: University Libraries; Professional; International; Wisconsin; Stress; Ghana.